Carriage of Rifampicin- and Multidrug-Resistant Pseudomonas aeruginosa in Apparently Healthy Camels: A View Through a Zoonosis Lens - Dalia Hamza; Hala M. Zaher (Microbiology Research)
Pseudomonas aeruginosa poses a significant global concern in human and veterinary medicine due to its resistance to multiple antimicrobials. Limited research has been carried out on rifampicin-resistant P. aeruginosa, particularly in food-producing animals such as camels. Therefore, the purpose of this study was to investigate the occurrence of rifampicin- and multidrug-resistant P. aeruginosa in apparently healthy camels. Nasal swabs and tissue samples were collected from one hundred apparently healthy slaughtered camels, and they were subjected to bacteriological isolation and identification of P. aeruginosa. Antimicrobial susceptibility testing was performed, followed by phenotypic and genotypic detection of ESBL-producing P. aeruginosa isolates. Twenty-two P. aeruginosa strains were investigated for the rpoB gene, including rifampicin-resistant isolates. P. aeruginosa was found in 16% (16/100) of the investigated apparently healthy slaughtered camels. P. aeruginosa was confirmed in sixteen and six isolates from nasal swabs and tissue samples, respectively, by pigment production on cetrimide agar. The most predominant beta-lactamase-encoding gene in twenty-two ESBL-producing isolates was blaPER (40.9%), followed by blaCTX-M (36.4%), blaTEM (31.8%), and blaSHV (27.3%). Multidrug resistance was identified in 54.5% (12/22) of P. aeruginosa isolates. The rpoB gene was detected in 11 (50%) out of 22 P. aeruginosa strains, with eleven positive isolates being regarded as rifampicin-resistant. Furthermore, phylogenetic analysis of a rifampicin- and multidrug-resistant P. aeruginosa rpoB gene sequence revealed a genetic relatedness to P. aeruginosa strains retrieved from human clinical cases. In conclusion, this study provides a snapshot on the occurrence of rifampicin- and multidrug-resistant P. aeruginosa among apparently healthy camels. In line with a possible risk of animal-to-human transfer, further molecular studies on rifampicin-resistant P. aeruginosa in animals are required to better understand and combat this serious zoonotic pathogen.